Extraction of Flavonoids From Natural Sources Using Modern Techniques - Chaves, Jaísa Oliveira; de Souza, Mariana Corrêa; da Silva, Laise Capelasso; Lachos-Perez, Daniel; Torres-Mayanga, Paulo César; Machado, Ana Paula da Fonseca; Forster-Carneiro, Tânia; Vázquez-Espinosa, Mercedes; González-de-Peredo, Ana Velasco; Barbero, Gerardo Fernández; Rostagno, Mauricio Ariel (Frontiers in Chemistry, 2020)
Flavonoids are one of the main groups of polyphenols found in natural products. Traditional flavonoid extraction techniques are being replaced by advanced techniques to reduce energy and solvent consumption, increase efficiency and selectivity, to meet increased market demand and environmental regulations. Advanced technologies, such as microwaves, ultrasound, pressurized liquids, supercritical fluids, and electric fields, are alternatives currently being used. These modern techniques are generally faster, more environmentally friendly, and with higher automation levels compared to conventional extraction techniques. This review will discuss the different methods available for flavonoid extraction from natural sources and the main parameters involved (temperature, solvent, sample quantity, extraction time, among others). Recent trends and their industrial importance are also discussed in detail, providing insight into their potential. Thus, this paper seeks to review the innovations of compound extraction techniques, presenting in each of them their advantages and disadvantages, trying to offer a broader scope in the understanding of flavonoid extraction from different plant matrices